Komunikační strategie Vietnamců - Domažlice - Thomayerová, Jana (Lidé města, 2004)
In March 2003, a research was carried out in the Stall Trading Section of Domažlice Municipal Authority with the aim of describing the strategy Vietnamese stallholders adopt in dealing with Czech authorities, namely in a difficult situation resulting from the Local Council's decision to reduce the number of stalls in traditional markets on the Town Square. The situation had to be defused by female clerks of the Section. The research was conducted by employing a method of disinterested observation. It was found out that Vietnamese traders mostly followed a policy of pretending they were unable to understand what clerical workers were telling them. In this context, a considerable persistence and pushiness of tbe Vietnamese was noticeable, which often made the clerical workers lose their temper. In order to push their demands, the Vietnamese kept repeating the same arguments, which more often than not were untrue. The Vietnamese were never first to ask questions, always waiting for the clerks to begin. Whenever an individual trader had failed, the Vietnamese negotiated as a group, which always had its own speaker. Only when they were threatened that the police would be called, did they immediately leave the market place. When they succeeded in their negotiations, they used a policy of pretending a subordinace position, expressed by nodding, agreeing, bows or repeated greetings.